EFFECT OF RED SEAWEED EXTRACT (KAPPAPHYCUS ALVAREZII) SUPPLEMENTATION ON FEED TOWARDS MICROBIAL COMMUNITIES AND RESISTANCE TO VIBRIO SP., SALINITY STRESS, AND TEMPERATURE STRESS OF WHITELEG SHRIMP (LITOPENAEUS VANNAMEI) IN THE POST LARVAE PHASE - Irsa Masyrifani, Miftakhul
Whiteleg shrimp (Litopenaeus vannamei) is one type of shrimp that is widely cultivated in Indonesia. There are several obstacles faced in whiteleg shrimp culture, such as Vibriosis disease caused by Vibrio sp. One alternative to overcome this problem is to enhance shrimp resistance to Vibrio sp. and environmental stress by providing feed supplementation made from red seaweed extract (Kappaphycus alvarezii) with a certain concentration. The aims of this study is to determine the optimum concentration of feed suplementation addition in increasing shrimp resistance to Vibrio sp. challenge test, salinity stress test, and temperature stress test by measuring biological, water quality, and microbial community parameters. In this study, stocking densities 65 PL/L were used and tested three different variations treatments of feed suplementation concentration, (1) Sp1; (2) Sp2, and (3) commercial feed without the addition of feed suplementation as a control. Vibrio sp. challenge test was performed for 7 days while the salinity stress and temperature stress tests were performed for 3 hours. The results showed that the highest specific growth rate (SGR), feed conversion ratio (FCR), total biomass, productivity, final weight, dan final length was shown by Sp1 treatment, while the highest resistance to Vibrio sp., salinity stress, and temperature stress was shown by Sp2 treatment and significantly different from other treatments (P <0.05), respectively 79.33 ± 0.14%; 98.00 ± 0.02%; and 70.67 ± 0.05%. The results of water quality in the Vibrio sp. challenge test period showed that all treatment had optimum ammonium, nitrite, nitrate, and DO concentration. Total abundance of Vibrio sp. increased from day 1 to day 7 of the Vibrio sp. challenge test period, where the lowest abundance of Vibrio sp. in shrimp samples and water samples showed by Sp2 treatment, respectively 7.5x105 CFU/mL and 1.1x106 CFU / mL. Based on this study, Sp1 treatment showed the most optimum biological parameters, while Sp2 treatment showed the highest resistance to Vibrio sp., salinity stress, and temperature stress compared to other treatments.